2022
DOI: 10.1155/2022/3073121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Clinical Effects of the Cable‐Pin System and Kirschner Wire Tension Band (TBW) Internal Fixation in the Treatment of the Olecranon Fracture

Abstract: Objective. To explore the clinical effects of the cable-pin system and Kirschner wire tension band (TBW) internal fixation in the treatment of the olecranon fracture. Methods. Fifty patients with an olecranon fracture were treated in our hospital from April 2018 to March 2020. Patients were randomly divided into control and study groups. The control group was fixed with TBW, and the study group was fixed with the cable-pin system. The operation, the circumference difference between the injured limb and the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, owing to the low subcutaneous fat in the olecranon area and high incision tension, the needle tip can easily penetrate the skin, infecting the incision ( 12 ). Furthermore, this technology can loosen or displace the Kirschner needle, break the steel wire, and cause needle tail irritation of the skin and soft tissues, causing pain ( 13 ). In our study, grafts loosened in three cases, causing the tips of the Kirschner needle to touch the skin surface without fracture displacement or local infection during subsequent follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, owing to the low subcutaneous fat in the olecranon area and high incision tension, the needle tip can easily penetrate the skin, infecting the incision ( 12 ). Furthermore, this technology can loosen or displace the Kirschner needle, break the steel wire, and cause needle tail irritation of the skin and soft tissues, causing pain ( 13 ). In our study, grafts loosened in three cases, causing the tips of the Kirschner needle to touch the skin surface without fracture displacement or local infection during subsequent follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Negative emotions and sleep disorders can increase the sensitivity of pain and cause pain. Severe pain can cause irritability and raise the risk of nurse-patient disputes [ 19 , 20 ]. In this study, the pain score of patients 24 h, 48 h, 72 h after the operation were analyzed, and it was found that the comprehensive rehabilitation nursing intervention VAS score at each time point were considerably lower than the conventional nursing intervention; after intervention, HAMD and HAMA scores were lower than those of routine nursing intervention, and nursing satisfaction score, GCQ score and excellent rate of related knowledge mastery were higher than those of routine nursing intervention.…”
Section: Discussionmentioning
confidence: 99%